Pressure Changes in Pipe Transporting Mixture of Iraqi Crude Oils (Gathering System) - Abdul-Ameer , Maha R.; Daway, Mohammed M. (Journal of Petroleum Research and Studies, 2013)
A study has been done to represent the pressure changes along gathering system in pipelines transporting Iraqi’s crude oils; the study is divided into four parts. The first part represents the calculations of pressure drop in pipelines transporting petroleum fluid from the well head to a gathering point. In this part, there is a two-phase flow (gas and liquid). The calculations of pressure change in this part depends upon determination of some properties such as liquid and gas density, liquid and gas viscosity, liquid hold up and friction factor. Determining the liquid hold up and then pressure drop are achieved using two methods, the first method is modified Beggs and Brill correlation, depending on three assumed flow patterns. The second is Aziz et al. correlation, depending on three flow patterns also but are different to that of modified Beggs and Brill. While a method of Colebrook used in determination of two-phase friction factor. The results of two-phase flow calculations show that modified Beggs and Brill correlation (having error of 0.26%) better than Aziz et al. correlation (having error of 0.55%). In the second part there are calculations of pressure change in liquid flow in a pipeline from the gathering point to the first stage of separators. In this part Colebrook correlation is used to determine the friction factor, Brill and Mukherjee method is used for calculation of pressure change. Mukherjee and Brill method gave good results with respect to the pressure drop of flow in the axial pipeline after the gathering point of the actual field data. The third part deals with the networking in pipelines, types of gathering systems presented and discussed, the calculations of pressure change in a simple gathering system is studied. The fourth part discusses optimization techniques; Constrained Rosenbrock is used to find optimum pressure which gives favorable oil properties. They have been achieved with some assumptions; they are: Minimum Produced gas oil ratio. Minimum formation volume factor. Maximum API gravity. Finally, two computer programs are developed. Each program performs all the calculations of the four parts. The first program is developed using FORTRAN language, while the second is developed using Visual Basic language.